Correlation between Toxoplasma gondii and Cytomegalovirus infections and somatic symptom in community - Isti Anindya; Budi Mulyono; Carla R. Marchira; Marsetyawan HNE Soesatyo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
The prevalence of Toxoplasma gondii and Cytomegalovirus (CMV) infections are high in the world. Indonesia is one of the countries with high prevalence of these infections varied from 20 to 63%. The T. gondii and CMV infections infections can be chronic and cause maternal and fetal deatht as well as infant defects. Previous clinical study reported that chronic infections can cause somatic symptoms indicating psychological stress. The aim of this study was to evaluate the correlation between T. gondii and CMV infections with somatic symptoms. This was an observational study with a cross sectional design involving 103 eligible patients with seropositive IgG T. gondii or and CMV from six cities in Java, Indonesia. The presence of somatic symptoms was detected by using somatic symptoms inventory (SSI) questionnaire. Logistic regression analysis was used to evaluate the correlation. The percentage of patients with somatic symptoms (SSI score >48) in seropositive groups of IgG anti- T. gondii, anti-CMV, anti- T. gondii and CMV were 70.0; 62.2 and 36.2%, respectively. In addition, the prevalence ratio (PR) for each group were 1.333, 1.178, and 0.954, respectively. No significantly different in PR was observed in this study (p>0.05). In conclusion, the T. gondii and CMV infections are not correlted with the somatic symptoms.